Effect of Temperature and Duration of Gasbio Heat Energy on Bee Pollen Bioactive Compounds and Bee Propolis Extraction Trigona sp - Yasri Rahmawati, Yasri; Mochammad Junus (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Processing of dried bee pollen and propolis extraction to optimize the use of processed by-products of Trigona sp bees in the general public by utilizing biogas as heat energy. This research uses bee pollen and raw bee propolis (Trigona sp). The aim of the research was to determine the effect of temperature and length of time for drying bee pollen and propolis extraction on bioactive compounds. The research method used a completely randomized design (CRD) with 5 treatments and 3 replications, consist with (1) Bee pollen drying temperature with sunlight, 45 oC, 55 oC, 65 oC, and 75 oC, (2) Long oven time 3 days, 2,5 hours, 2 hours, 1 hour, and 15 minutes. Meanwhile, the treatment for propolis extraction with distilled water solvent is (1) Temperature 70 oC, 75 oC, 80 oC, 85 oC, and 90 oC, (2) Length of extraction time is 220 minutes. Data were analyzed using Variant ANOVA. If there is a significant difference and effect (P<0.05) or highly significant (P<0.01), then proceed with least significant difference test. Dried bee pollen research results the best bioactive compounds were obtained at a temperature of 65 oC (T3) with protein content (14.09 %), total phenol (1.314 mgGAE/g), and antioxidant content (53.97 ug/mL). The best results for propolis extraction were at a temperature of 70 oC (T0) with antioxidants (21.15ug/mL) and total phenolics (0.357 mgGAE/g). Gasbio can be used as an alternative heat for drying bee pollen and propolis extraction, but when use gasbio must determine the right temperature and time.